Pelatihan dan Pemberdayaan Reverse engineering Bagi Siswa SMK untuk Mendukung Revolusi Indusri 4.0 - Riyadi Muslim; Herman Saputro; Ranto Ranto; Ngatou Rohman; Riina Syvarulli (Yayasan Literasi Sains Indonesia, 2025)
Rapid growth is being experienced by the automotive industry in Indonesia. A significant challenge for vocational school education is the increasing demand for skilled and relevant human resources in order to respond to the challenges of the Industrial Revolution 4.0. Students at SMK Daya Wangsa Wonogiri's Heavy Equipment Engineering Vocational School have difficulty mastering product design competencies due to limited technology and learning methods that focus on reverse engineering technology. Therefore, reverse engineering training based on industrial products is necessary to provide students with various product development skills. This training method includes: 1) Introduction to reverse engineering; 2. Use of 3D scan as an advanced tool in reverse engineering; 3. Reverse engineering project; 4. Project presentation, and 5) Evaluation. This program is expected to provide technical skills that are competitive with the current state of the automotive industry. Results show that students exhibit excellent technical perception, attitude, and motivation toward this technology. This program can support improving the quality of vocational education through reverse engineering technology. In the future, it can establish SMK as a center of excellence by promoting applied technology.